Revised typification of Gomphrena argentina (Amaranthaceae s. str.) - Alvarenga Braga, João Marcelo (Phytotaxa, 2018)
Gomphrena Linnaeus (1753: 224) (Gomphrenoideae Schinz, Amaranthaceae Juss.) is a genus including about 120 species, with center of diversity in the New World, and higher species richness in Central Andes, in argentinean and bolivian Puna, and Caatinga, and Cerrado habitats in Brazil (see e.g., Muller & Borsch 2005; Sánchez del Pino et al. 2009).